Community voices: Exploring beliefs, attitudes, practices and recommendations for improving stroke prevention and stroke care in rural and urban communities in Nigeria - Ezinne O. Uvere; Carolyn Jenkins; Ezinne S. Melikam; Oyedunni S. Arulogun; Omotolani T. Ajala; Adewale E. Ayodele; Olayinka J. Adebajo; Osimhiarherhuo Adeleye; Olumayowa Ogunronbi; Chukwuemeka Nwimo; Michelle Nichols; Oluwafemi A. Popoola; et al. (PLoS ONE, 2026)
Introduction Globally, stroke is a leading cause of mortality with higher incidence in low- and middle-income countries. However, stroke beliefs and knowledge among community partners are essential considerations for tailoring of interventions in West Africa. Purpose To describe differences in beliefs, attitudes, and practices related to stroke risks, prevention, and care delivery from alternative/complementary providers/healers, orthodox/modern medicine/health care providers, community members and leaders in Nigeria. Methods Six focus groups with community members and leaders (n = 57) and key informant interviews with health providers (n = 24) from alternative/complementary and orthodox/modern medicine providers were conducted to qualitatively explore beliefs, attitudes, practices, and recommendations related to stroke in urban (Ibadan) and rural (Ibarapa) communities in Nigeria. The Socio-Ecological Model guided selection of participants, and the Health Belief Model guided the development of questions for participants. Results Participants perceived stroke as disabling, though manageable, and having higher odds of repeat stroke for survivors. High blood pressure, stress, sleep issues, heredity, and lifestyle factors were some stroke risk factors perceived by participants from both sites although God, witchcraft/evil people were reported by rural participants. Hospital visits and consumption of herbal concoction, self-medication and visit to church for prayers were some actions taken to manage stroke by both urban and rural participants. Low literacy levels, limited funds, fear of and distance to hospitals, and absence of insurance were some barriers to uptake of recommendations from orthodox medicine practitioners which are drivers to unorthodox practitioners. To improve stroke care and prevention across communities, free risk factor screening, indigenous stroke awareness programs via print, audio-visual and electronic media were suggested by all participants. Conclusion Diverse beliefs and practices are related to stroke risk factors, prevention and care and barriers with obtaining care. There is need to work across systems to improve stroke prevention and care in communities.